2017
DOI: 10.1016/j.jadohealth.2016.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Research in the Integration of Behavioral Health for Adolescents and Young Adults in Primary Care Settings: A Systematic Review

Abstract: Despite the recognition that behavioral and medical health conditions are frequently intertwined, the existing health care system divides management for these issues into separate settings. This separation results in increased barriers to receipt of care and contributes to problems of under-detection, inappropriate diagnosis, and lack of treatment engagement. Adolescents and young adults with mental health conditions have some of the lowest rates of treatment for their conditions of all age groups. Integration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 71 publications
1
48
0
Order By: Relevance
“…approaching adulthood, a teenager faces many difficult tasks, and some of these can be overwhelming. in general, youth itself is considered a risk factor for mental problems [6,8]. additionally, studies revealed that the treatment rate among adolescents and young adults with mental health problems is especially low.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…approaching adulthood, a teenager faces many difficult tasks, and some of these can be overwhelming. in general, youth itself is considered a risk factor for mental problems [6,8]. additionally, studies revealed that the treatment rate among adolescents and young adults with mental health problems is especially low.…”
Section: Discussionmentioning
confidence: 99%
“…one of the problems related to mental disorders in adolescents that emerged from a review of literature is the low rate of youngsters receiving appropriate care. research has shown that only 50% of adolescents who suffer from severe impairment related to mental health problems is under specialist care [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expansion of the medical home team to include a mental health provider is financially feasible in some payment environments and clinically beneficial to patients and families. [94][95][96][97] In addition, it offers PCCs the benefit of crossdisciplinary learning through experiences such as collaborative care planning, clinical problem solving, and comanagement of patients with mental health morbidities and comorbidities. [98][99][100] These integrated models of care in which a licensed mental health specialist is on-site in a primary care practice have shown promise in improving access to mental health care for patients, improving patient functioning and productivity, and improving patient and provider satisfaction.…”
Section: Education Of Experienced Cliniciansmentioning
confidence: 99%
“…5 Asarnow et al's 6 systematic review revealed that, compared with youth receiving usual care, youth receiving integrated care were 66% more likely to have better behavioral health outcomes. A systematic review examining the integration of behavioral health within clinical settings 7 found the number of studies on adolescents and young adults was low; accordingly, the authors recommend research on strategies to increase the likelihood of integrated care adoption and implementation.…”
mentioning
confidence: 99%